Major phosphorus in soils is unavailable, yet critical for plant development - Beckley IKHAJIAGBE; Geoffrey O. ANOLIEFO; Ogochukwu F. OLISE; Fabian RACKELMANN; Milena SOMMER; Isaac J. ADEKUNLE (Notulae Scientia Biologicae, 2020)
Phosphorus (p) is a chemical component that has a concentration in the world’s land mass of around one gram for each kilogram. 85% to 95% of cellular phosphorus is available in the vacuole, 31p-nmr examinations uncovers the inadequacy of inorganic phosphorus (pi) efflux from the vacuole to make-up for a fast reduction of the cytosolic pi focus during phosphorus starvation. Activities of phosphorus use involve biogeochemical mechanisms of phosphorus in soil, the phosphorus cycle, chelation of iron (Fe), manganese (Mn) and aluminium (Al) and their subsequent removal from forming insoluble phosphorus compounds, transformation of phosphorus in the soil, and fixation of phosphorus in the soil. Phosphorus utilisation occur through solubilization by microbes which could be bacteria, fungi or bio-fertilizers that produce phytohormone, siderophores and antibiotics. However, factors affecting phosphorus solubilization are pH and temperature which are key predominant players for phosphorus adsorption dynamics from the soil and rhizosphere by plants, soil phosphorus transformation, spatial availability and acquisition of soil phosphorus, root architecture, bioavailability and acquisition of soil phosphorus, phosphorus cycling and bioavailability in soil-plant systems, its chemistry as well as its final uptake and utilization by plants. Overall, the phosphorus nutrition of plants is majorly monitored by phosphorus dynamics in the soil/rhizosphere-plant continuum. Given the usefulness of phosphorus to plants and its importance as a strategic resource, a better understanding of phosphorus dynamics in the soil/rhizosphere-plant continuum is necessary to lead the establishment of integrated phosphorus-management strategies involving manipulation of soil and rhizosphere activities, development of phosphorus-efficient crops, and improving phosphorus-recycling efficiency in the future.